Changes in mucosal and humoral atopic-related markers and immunoglobulins in elite cyclists participating in the Vuelta a Espana - McKune, A. J.; Smith, L. L.; Semple, S. J.; Wadee, A. A.; Fickl, H.; Villa, J. G.; Gomez-Gallego, F.; San Juan, A. F.; Lucia, A. (International Journal of Sports Medicine, 2006)
Atopic-related factors, humoral and mucosal immunoglobulins (Ig), and cortisol were measured in 17 professional cyclists competing in the 2003 Vuelta a España (a three-week multi-stage race). Venous blood and saliva samples were obtained the morning before the start of the race (T0), on the first rest day after 10 days of racing (T1), and before the start of the last stage after 21 days of racing (T2). Atopic-related factors, IgE, eosinophil cationic protein (ECP), and eosinophils, were significantly altered during the race. Serum IgE (T1: + 10 %) and ECP (salivary, T1: 113 % and serum, T2: 155 %) were significantly increased, while eosinophils (T1: - 32 %, T2: - 55 %) were significantly lower, than pre-race levels. Salivary sIgA secretion rate was significantly decreased at T2 (- 36 %). Pearson product-moment correlations revealed a modest correlation between salivary sIgA and salivary ECP (T1: r = 0.30; T2: r = 0.48; p < 0.01). Serum IgM, total IgG, IgG1, IgG2, IgA levels, at T1 and T2, and cortisol at T2, were significantly lower than pre-race levels. In conclusion, the elevation in IgE and ECP suggests an up-regulation of atopic-related factors in professional cyclists participating in the Vuelta a España. The correlation between salivary sIgA and salivary ECP indicates a role for sIgA in mediating mucosal inflammation. The alterations in Ig levels may indicate Ig isotype switching. An increasing state of hormonal fatigue may have influenced the observed immune alterations.